Reliability of short-term measurement of heart rate variability on rest in individuals with temporomandibular disorder - Rodrigo Costa Cutrim; Aldair Darlan Santos-de-Araújo; Cassius Iury Anselmo-e-Silva; Janaina de Oliveira Brito Monzani; Rudys Rodolfo de Jesus Tavarez; Maria Cláudia Gonçalves; Etevaldo Matos Maia-Filho; Audrey Borghi-Silva; Almir Vieira Dibai-Filho; Daniela Bassi-Dibai (Scientific Reports)
Abstract Individuals with temporomandibular disorder (TMD) experience autonomic dysfunction, which disrupts the balance between the sympathetic and parasympathetic nervous systems. This imbalance can result in altered heart rate variability (HRV) and other physiological disturbances. However, it is important to note that, to date, no research has investigated the inter- and intra-rater reliability of HRV measurements in individuals with TMD. The objective of this investigation was to analyze the intra- and inter-examiner reliability of HRV captured by a polar heart rate monitor in individuals with TMD. The RR interval, the time elapsed between two successive R-waves of the QRS signal on the electrocardiogram (RRi), were recorded during a 10 min period in a supine position using a portable heart rate monitor (Polar® V800 model). The data were transferred into Kubios® HRV standard analysis software and analyzed within the stable sessions containing 5 min sequential RRi. The intraclass correlation coefficient (ICC) ranged from 0.907 to 0.998 according to the intra-examiner analysis by Examiner 1 and 0.875 to 0.998 according to the intra-examiner by Examiner 2. The inter-examiner ICC ranged from 0.796 to 0.996. The coefficient of variation was up to 9.60 for Examiner 1 intra-examiner analysis, 11.95 for Examiner 2 intra-examiner analysis and 14.88 for inter-examiner analysis. The HRV analysis captured by a Polar cardio frequency meter presented adequate reliability when considering different times and examiners. Intra-examiner reliability showed ICC values ranging from 0.842 to 0.999, and inter-examiner reliability ranged from 0.796 to 0.994. Bland–Altman plots indicated good agreement with minimal bias. Coefficients of variation were below 10% for most variables.